Use of industrial waste materials for 3D printing of sustainable concrete: A review. (15th March 2022) - Dey, Dhrutiman; Srinivas, Dodda; Panda, Biranchi; Suraneni, Prannoy; Sitharam, T.G.
Abstract: This paper provides a comprehensive review of the utilization of industrial wastes in 3D concrete printing processes. Concrete 3D printing processes are introduced, highlighting the need for unique material requirements. The literature on the different wastes that have been used for producing 3D printable mixtures is reviewed, including waste generation, material properties, and the roles of these materials in improving the fresh properties needed for concrete printing. Factors affecting successful utilization of these waste materials in 3D printable concrete are discussed in addition to their environmental impacts. This paper underlines the positive impacts of using industrial wastes for improving the sustainability of 3D printable concrete. It is expected that printable concrete formulations containing high volumes of industrial waste (and chemical admixtures) can be developed to improve the sustainability index of this emerging construction technique. Graphical abstract: Image 1 Highlights: o Critical review of 3D printed concrete made with industry waste is presented. o Factors affecting successful utilization and effects of these waste materials are discussed. o Sustainability assessment of 3D printable mixes is presented. o The challenge is to produce high performance 3D printable concrete using high volume of industry waste.